Technological Strategies and Dynamics of Innovation of the Agrifood Companies in Brazil (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4906.47-75.This paper analyzes the behavior and the strategies of Brazilian agro-food companies, from 1998 to 2005, focusing on technological and innovative aspects. The main database used to construct the indicators was the Industrial Survey of Technological Innovation (PINTEC-IBGE). The methodology was also based on extensive literature review. It was observed that the food and beverage sector was characterized by low indicators of technological efforts, but high indicators of results, showing that this industry has performed the role of technological diffuser and actuated little as generator of knowledge. The reduced technological efforts, however, have showed sufficiency in presenting significant economic results, visualized by the increase on the participation of the innovative firms on the industrial transformation value and on the exported value by the companies of the sector.